OBSCENE LEXICON IN FOREIGN RESEARCHES - Tkachivska, M. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article presents the analyses of the foreign scientific researches concerning the problem of obscene words. It conveys an observation of the scientific papers dwelling on the issue of erotic and obscene lexical units in general, as well as the usage of erotic and obscene lexical units in literature. Eroticism in literature and folklore (including poetry, prose, plays, proverbs and sayings etc.) is interpreted by society and writers in different ways, depending on the epoch. It has also been a subject under scrutiny for literary critics and reviewers, along with the scientists, who pay their attention to the usage of the obscene language in both folklore and literature of different ages. Usually medieval times are characterized by a strong influence of church, which determined a common public opinion, though in the early Middle Ages the church only started to dominate (in terms of existence of a sexual freedom). The majority of researchers pays attention to the fact that the XX century is characterized by a considerable change in a public opinion concerning morality, public relationships, nudity etc. In the post-modern period we talk about both direct understanding and interpretations, as well as hidden messages, which require certain analyses and which are supposed to stimulate an intellectual collaboration with a recipient. The analyses of the current state of researches on the given topic show some considerable learned interest in the topics which have been considered a taboo not a long time ago. The article highlights the importance of the further research of the obscene language, for the analyses of the already existing works on it shows a growing need to discover peculiarities of the usage of the obscene language in literature.